CERITA “SAMUDRAMANTHANA” PADA STRUKTUR BANGUNAN PADMASANA DI PURA AGUNG JAGATNATHA DENPASAR (Perspektif Pendidikan Agama Hindu) - Ferdinandus Nanduq; Sandika, Pande Kadek; A. A Diah Indrayani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Samudramanthana story is one of the mythical stories of Hinduism recorded in several Purana books, where there are figures and symbols that have their own meaning in the process of religious life, especially in the Padmasana building at Jagatnatha Temple, Denpasar. The issues to be discussed include: (1) What is the form of the visualization of religious values in the Samudramanthana story in the Padmasana building at the Agung Jagatnatha Temple Denpasar?, (2) What are the implications of the visualization of religious values in the Samudramanthana story in the Padmasana building at the Agung Jagatnatha Temple Denpasar for education? Hindu religion?. This study aims to find out: (1) the form of visualization of religious values in the Samudramanthana story in the Padmasana building at Pura Agung Jagatnatha Denpasar, (2) The implications of the visualization of religious values in the Samudramanthana story in the Padmasana building at Pura Agung Jagatnatha Denpasar for Hindu religious education. The theory used to analyze the problem is the theory of Hermeneutics from Ricocur and the theory of Social Learning from Albert Bandura. The subject of this research is the Stakeholder/Stakeholder of Pura Agung Jagatnatha Denpasar. Data collection methods are non-participant observation, open interviews, literature studies and documentation. The data obtained were analyzed using qualitative analysis methods with reduction steps, data presentation, and drawing conclusions. The results of the study show that the form of visualization of religious values in the Samudramanthana story in the Padmasana building at the Agung Jagatnatha Denpasar Temple, namely considering that there are very many figures or symbols in the Samudramanthana story that are visualized in the Padmasana building, especially the Padmasana building at the Agung Jagatnatha Temple Denpasar. The implication of the visualization of religious values in Samudramanthana's story in the Padmasana building at Pura Agung Jagatnatha Denpasar for Hindu religious education, is to provide an overview of the conception of the three basic frameworks of Hinduism namely tattwa, morals, and ceremonies